Paracoccidioidomycosis surveillance and control - Mendes, Rinaldo Poncio [UNESP] (2010)
São Paulo State Univ, UNESP, Univ Estadual Paulista, Dept Trop Dis,Botucatu Med Sch,Fac Med Botucatu, BR-18618000 Botucatu, SP, Brazil